Misinformation Across Digital Divides: Theory And Evidence From Northern Ghana. Issue 483 (29th April 2022) - Gadjanova, Elena; Lynch, Gabrielle; Saibu, Ghadafi
Abstract: Social media misinformation is widely recognized as a significant and growing global problem. Yet, little is known about how misinformation spreads across broader media ecosystems, particularly in areas with varying internet access and connectivity. Drawing on research in northern Ghana, we seek to address this gap. We argue that 'pavement media'—the everyday communication of current affairs through discussions in marketplaces, places of worship, bars, and the like and through a range of non-conversational and visual practices such as songs, sermons, and graffiti—is a key link in a broader media ecosystem. Vibrant pavement and traditional media allow for information from social media to quickly cross into offline spaces, creating a distinction not of the connected and disconnected but of first-hand and indirect social media users. This paper sets out how social, traditional, and pavement media form a complex and deeply gendered and socio-economically stratified media ecosystem and investigates its implications for how citizens differentially encounter, process, and respond to misinformation. Based on the findings, we argue that efforts intended to combat the spread of misinformation need to move beyond the Western-centred conception of what constitutes media and take different local modalities of media access and fact-checking into account.